2021
DOI: 10.3389/fonc.2021.658331
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of Docetaxel or Abiraterone Effectiveness and Predictive Markers of Progression Free Survival in Metastatic Castration-Sensitive Prostate Cancer

Abstract: BackgroundBoth Docetaxel (DOC) and Abiraterone (ABI) improve the survival of men with metastatic, castration sensitive prostate cancer (mCSPC). However, the outcome among mCSPC patients is highly variable, while there is a lack of predictive markers of therapeutic benefit. Furthermore, there is limited data on the comparative real-world effectiveness of adding DOC or ABI to androgen deprivation therapy (ADT).MethodsWe conducted a retrospective analysis of 121 mCSPC patients treated at Odette Cancer Centre (Tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
0
3
2
Order By: Relevance
“…It is noteworthy, that the magnitude of the benefit in the current study, as well as in the study of Weiner et al, cannot be directly compared to the magnitude of survival benefit recorded in phase 3 trials for specific systemic approaches for metastatic prostate cancer (18,19). It is of note, that the magnitude of the survival benefit in most of phase 3 studies addressing overall survival in metastatic prostate cancer was greater than the magnitude recorded in our study, as well as that recorded in the study of Weiner et al and other small scale institutional studies (20)(21)(22).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…It is noteworthy, that the magnitude of the benefit in the current study, as well as in the study of Weiner et al, cannot be directly compared to the magnitude of survival benefit recorded in phase 3 trials for specific systemic approaches for metastatic prostate cancer (18,19). It is of note, that the magnitude of the survival benefit in most of phase 3 studies addressing overall survival in metastatic prostate cancer was greater than the magnitude recorded in our study, as well as that recorded in the study of Weiner et al and other small scale institutional studies (20)(21)(22).…”
Section: Discussioncontrasting
confidence: 69%
“…It is of note, that the magnitude of the survival benefit in most of phase 3 studies addressing overall survival in metastatic prostate cancer was greater than the magnitude recorded in our study, as well as that recorded in the study of Weiner et al. and other small scale institutional studies ( 20 22 ).…”
Section: Discussioncontrasting
confidence: 57%
“…Briones et al . studied the survival of mCSPC patients after receiving docetaxel or abiraterone combination therapy and found that age at diagnosis of mCSPC, PSA90 at 3 months, and LATITUDE risk classification are prognostic factors of PFS 18 …”
Section: Discussionmentioning
confidence: 99%
“…17 Briones et al studied the survival of mCSPC patients after receiving docetaxel or abiraterone combination therapy and found that age at diagnosis of mCSPC, PSA90 at 3 months, and LATITUDE risk classification are prognostic factors of PFS. 18 However, these traditional markers all have their own limitations. Gleason score mainly reflects the degree of malignancy of the primary lesion and cannot reflect tumor burden in the whole body of metastatic prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a large randomize controlled trial, larger OS benefits were shown in abiraterone acetate and apalutamide treatment whereas enzalutamide was associated with a greater improvement in PFS. Moreover, large population retrospective studies have found several factors related to ARSI efficacy, including tumor volume, level of prostate specific antigen (PSA) at diagnostic, age and visceral metastasis 16 .…”
Section: Introductionmentioning
confidence: 99%